(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article describes and discloses the methodological problems of countering cyber terrorism, along with ensuring information security (hereinafter IS) in the activities of society, the state, and individual citizens. It also presents the main provisions, concepts and definitions, terms, methods of ensuring information security, various types and sources of information security threats, describes the organizational and legal methodological support of information security for the activities of society and systems in various areas of its life cycle. At the same time, the use of high technologies at the same time imposes a high responsibility on the owners of information systems; without the proper level of security, it is impossible to guarantee the confidentiality of entrusted and processed data. As you know, in the conditions of active and large-scale introduction of information technologies in all areas of public administration, the urgency of this problem increases. At the same time, it is necessary to emphasize that the issues of ensuring information security and the problems of countering cyber terrorism have not received a conceptual approach at the doctrinal and legislative level, although they are touched upon in a number of some documents.